2015
DOI: 10.1159/000439097
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma in Cirrhosis: Value of Hepatocyte Specific Magnetic Resonance Imaging

Abstract: Background: The diagnosis of intrahepatic cholangiocellular carcinoma (ICC) remains elusive at imaging, which is a critical issue in cirrhotic patients in whom a diagnosis of hepatocellular carcinoma (HCC) can be established only by imaging. Aim: The aim of the study was to evaluate the potential of MRI in the diagnosis of ICC in cirrhosis using ‘hepatocyte-specific' Gadolinium (Gd)-based contrast agents. Methods: Sixteen histologically proven and retrospectively identified ICCs on cirrhosis were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…A recent comparative study (18) of IHCC and HCC also reported a dramatic reduction in the misclassification rate of IHCC as HCC (from 20% to 4%) using PVP washout instead of conventional washout, although this result obtained from IHCCs mainly in noncirrhotic liver may not adequately address the findings of IHCCs in patients with cirrhosis. A prior study including 15 IHCC nodules in cirrhosis also reported that none of the IHCCs showed concurrent AP enhancement and PVP washout (32). The results in our study support a recent statement by LI-RADS that recommends determining the washout during the PVP rather than during the TP at gadoxetic acid-enhanced MR imaging for a reliable diagnosis of HCC (12,15).…”
Section: Subgroup Analysis Of Surgically Proven Ihccs and Matched Hccssupporting
confidence: 88%
“…A recent comparative study (18) of IHCC and HCC also reported a dramatic reduction in the misclassification rate of IHCC as HCC (from 20% to 4%) using PVP washout instead of conventional washout, although this result obtained from IHCCs mainly in noncirrhotic liver may not adequately address the findings of IHCCs in patients with cirrhosis. A prior study including 15 IHCC nodules in cirrhosis also reported that none of the IHCCs showed concurrent AP enhancement and PVP washout (32). The results in our study support a recent statement by LI-RADS that recommends determining the washout during the PVP rather than during the TP at gadoxetic acid-enhanced MR imaging for a reliable diagnosis of HCC (12,15).…”
Section: Subgroup Analysis Of Surgically Proven Ihccs and Matched Hccssupporting
confidence: 88%
“…In our population MRI examination has demonstrated the high sensitivity (100%) in detecting neoplastic lesions, including in those lesions <1 cm. Our results are in line with many studies that reported a sensitivity of breast MRI between 86-97% with a high diagnostic accuracy of the early stages (19,(25)(26)(27)(28)(29)(30)(31). However, the combination of clinical breast examination, mammography and US has not sufficiently sensitive in high-risk women, as demonstrated by many series (11,25) and consequently, has a minor role in patients with hereditary predisposition to the disease.…”
Section: Discussionsupporting
confidence: 86%
“…206,207 This definition improves the capacity of CEUS to identify malignant lesions such as CC (which are often not identified as definitively malignant by CT and MRI using the conventional vascular criteria. [208][209][210] This new CEUS criteria for HCC has already been adopted in Italy (Italian Association for the Study of the Liver 211 and by the American College of Radiology in the USA. 206,212 A very recent large retrospective study in more than 1,000 lesions in cirrhosis, showed this new definition of the typical HCC pattern (corresponding to the LR5 classification according to LI-RADS for CEUS) has a positive predictive value for HCC of almost 99% (higher than the one achieved using the previous EASL and American Association for the Study of Liver Diseases (AASLD) criteria, corresponding to 94%) and positive likelihood ratio of 15.5, with no case of misdiagnosis with intrahepatic CC.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%